Evaluation of the Coolnet Placement Distance to Direct Evaporative Cooling to Increase Potato Seed Production in Aeroponic Systems with Root Zone Cooling in the Lowlands - Eni Sumarni; Priswanto Priswanto; Zaroh Irayani; Noor Farid (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Evaluation of the placement of the coolnet distance on direct evaporative cooling is needed in order to reduce the wilting percentage and improve seed production of potatoes. The aim of the study was to obtain the appropriate coolnet distance for the growth and development of aeroponic potato seedlings in evaporative cooling and root zone cooling applications in the tropical lowlands. The factors tested were: 1) Evaporative cooling (JEvap) distance: JEvap1 (25 cm from the top zone of the plant), JEvap2 (50 cm from the top zone), and Jevap3 (60 cm), and 2) Varieties (V): V1 (MZ), V2 (Granola K), V3 (Granola L). The design used was completely randomized design with 2 replications. Growth data and results were analyzed by the F test and continued with Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that the direct evaporative cooling method and the coolnet spacing of 50-60 cm which were integrated with root zone cooling created an air temperature at the top of the plant 26-28 °C, reduced the percentage of burnt wilting, and increased the number of tubers by an average of 31.4 to 41.7 tubers/plant. Keywords: Aeroponic, cooling system, growth environment, hidroponic, limited control.